Comparing brain-behavioral systems, early maladaptive schemas, and preservative thinking in women with and without pregnancy anxiety in the health center of Ardabil Province, Iran - Atadokht, Akbar; Daryadel, Seyed Javad; Samadifard, Hamid Reza; Moradi Kelarde, Sara; Heidarirad, Hadees (Chronic Diseases Journal, 2020)
BACKGROUND: Anxiety and depression in women during pregnancy could be associated with unfavorable consequences of pregnancy, such as premature and low-weight newborn birth. Current study was conducted aiming to compare brain-behavioral systems, early maladaptive schemas (EMSs), and preservative thinking in women with and without pregnancy anxiety. METHODS: The method of this research was causal-comparative. The population included of the whole pregnant women who had been referred to Urban Health Service Centers of Ardabil Province, Iran, in order to receive pregnancy period cares at first quarter of 2017. 30 pregnant women whose pregnancy anxiety had been diagnosed by mental health experts and the physicians of the center trough screening and administering Pregnancy-related Anxiety Scale (PrAS) were selected using cluster random sampling. 30 women without anxiety were matched with the women having pregnancy anxiety in terms of age, times of pregnancy, number of children, education level, and economic status. For data collecting, Huizink et al.’s PrAS, Young Schema Questionnaire (YSQ) of Welburn et al., the behavioral inhibition system/behavioral activation system (BIS/BAS) scale of Carver and White, and Ehring et al.’s Preservative Thinking Questionnaire (PTQ) were used. The obtained data were analyzed by multivariate analysis of variance (MANOVA) using SPSS software. RESULTS: The results of MANOVA showed that there was a significant difference between brain-behavioral systems, EMSs, and preservative thinking in women with and without pregnancy anxiety (P < 0.010). CONCLUSION: Since maladaptive schemas, brain-behavioral systems, and preservative thinking are higher in pregnant women with anxiety than pregnant women without anxiety, so counselling, supportive, and training programs are essential for vulnerable mothers.